2020
DOI: 10.1039/c9ra09524a
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of H1N1 influenza induced apoptosis by sodium selenite through ROS-mediated signaling pathways

Abstract: The high variability of influenza viruses has made it more difficult for people to cope with influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Viral infection is associated with oxidative stress through the induction of enzymes that produce harmful reactive oxygen species (ROS) ( 9 ). There is an increase of ROS in a cell model infected with the influenza AH1N1 RNA virus ( 35 ). Sodium selenite decreases the production of ROS and the induced cell apoptosis in these infected cells ( 36 ).…”
Section: Mechanisms By Which Sodium Selenite Could Act In Rna Virus Imentioning
confidence: 99%
“…Viral infection is associated with oxidative stress through the induction of enzymes that produce harmful reactive oxygen species (ROS) ( 9 ). There is an increase of ROS in a cell model infected with the influenza AH1N1 RNA virus ( 35 ). Sodium selenite decreases the production of ROS and the induced cell apoptosis in these infected cells ( 36 ).…”
Section: Mechanisms By Which Sodium Selenite Could Act In Rna Virus Imentioning
confidence: 99%
“…Other research on the anti-influenza A virus showed three compounds with antiviral activity related to the efficacy of Flos Trollii and antiviral activities of compounds isolated from Pinus densiflora (pine tree) in cell culture [13,14]. Recent research demonstrated the antiviral activity of ATR-002 and selenium supplementation against influenza A virus in the cell culture [15,16]. Also, Yejin Jang and his teammates showed that lambda-carrageenan (λ-CGN) could be a promising and preventive agent for several respiratory infections, especially influenza A virus and SARS-CoV-2 [17].…”
Section: D Cell Culture Application For Sars-cov Mers-cov H1n1 and Sars-cov-2mentioning
confidence: 99%
“…Viral infection is associated with oxidative stress through the induction of enzymes that produce harmful reactive oxygen species (ROS) (9). There is an increase of ROS in a cell model infected with the influenza AH1N1 RNA virus (35). Sodium selenite decreases the production of ROS and the induced cell apoptosis in these infected cells (36).…”
Section: Decrease In Viral-induced Cell Apoptosismentioning
confidence: 99%